Analisis Pembaruan Hukum Zakat Di Dalam Undang-Undang Nomor 23 Tahun 2011 Tentang Pengelolaan Zakat - Ichwan Ahnaz Alamudi; Ahmadi Hasan (Faculty of Sharia and Law Universitas Islam Nahdlatul Ulama, 2023)
In the management of zakat is necessary for a clear legal umbrella in the form of regulations on zakat which is the foundation in the management of zakat. Along with the times, the existing regulations are sometimes considered no longer accommodate the issue of zakat management in the field, therefore the latest regulations on zakat management are needed. This study aims to try to discuss various legal updates regarding zakat, especially in zakat law. This study uses a juridical-normative approach, which is an approach based on legislation, theories, and concepts related to legal coverage of regulations in the field of zakat. The results showed that there are various regulations on zakat, ranging from ministerial regulations, presidential regulations, government regulations to laws.